Ministry Of Finance Decree No. 329 For The Year 2017 Amending Certain Provisions of the Minister of Finance Decree No. 66 of the Year 2017 Concerning the Executive Regulations of the Value-Added Tax Law As Issued by Law No. 67 of The Year 2016 = وزارة المالية قرار رقم 329 لسنة 2017 بتعديل بعض أحكام قرار وزير المالية رقم 66 لسنة 2017 بشأن اللائحة التنفيذية لقانون الضريبة على القيمة المضافة الصادر بالقانون رقم 67 لسنة 2016 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic